Thermal behavior of waste tea pyrolysis by TG-FTIR analysis. (15th May 2016) - Tian, Linghui; Shen, Boxiong; Xu, Huan; Li, Fukuan; Wang, Yinyin; Singh, Surjit
Abstract: To investigate the kinetic behavior and the release of evolved gases in the pyrolysis process for waste tea, the technique of TG-FTIR at different heating rates was introduced in this study. The mass loss of the waste tea was divided into two steps: the volatilization of water at the temperature lower than 210 °C, and the volatilization of CO2 and organic compounds at the temperature range of 210–550 °C. FTIR (Fourier transform infrared) analysis indicated that CO2 was the main gas released from the thermal degradation of waste tea. Moreover, the evolved gases from the waste tea also included H2 O, CH3 COOH, C6 H5 OH, CC and so on. Three model-free models and three model-fitting models were applied to investigate the pyrolysis process of waste tea. According to the values of the activation energy by the three model-free models and the correlation coefficient from model-fitting models, the activation energy (207.96 kJ/mol ∼ 222.6 kJ/mol) and pre-exponential factor were determined for the pyrolysis of waste tea. The results of the model-fitting models indicated that three-dimension diffusion (spherical symmetry) model conformed to the pyrolysis mechanism of waste tea well. Highlights: Gases release rule in the waste tea pyrolysis was discovered by TG-FTIR analysis. The pyrolyzed gases included CO2, H2 O, CH3 COOH, C6 H5 OH, CC and so on. Three-dimension diffusion model conformed to the pyrolysis mechanism of waste tea well. The activation energy of waste tea pyrolysis was determined to be 207.96 kJ/mol ∼ 222.6 kJ/mol.